Isolation and Identification of Novel Streptococcus pluranimalium Isolated from Children with Upper Respiratory Infections in Mosul Hospitals, Iraq - Mahmood, Sura; Kahya, Hasan Faisal Hussein (Iraqi Journal of Science, 2022)
Streptococcus pluranimalium was first isolated in 1999. Recently, several case reports have been published that have revealed that S. pluranimalium can infect humans as well. The pathogenicity and pathophysiology of this pathogen is poorly studied and its characteristics are not well known. In this study, S. pluranimalium was first isolated and then identified from infants and children who suffered from upper respiratory infections. 90 samples were collected from nasopharyngeal cavity. Among them, 83 Streptococcus spp. isolates were identified. 3 out of which were biochemically and molecularly identified as S. pluranimalium. 16S rRNA sequencing based identification revealed that all isolates showed a very close identity match (92%) with subjected S. pluranimalium when blasted with gene bank database. Furthermore, the antibiotic susceptibility of S. pluranimalium towards ten antibiotics was conducted using Kirby-Bauer disk diffusion test. The results revealed that S. pluranimalium was 100% susceptible to penicillin, levofloxacin, and ofloxacin. However, other antibiotics showed diverse effects on S. pluranimalium.